Prosperity - Jane Golley; Linda Jaivin (ANU Press, 2018)
A 'moderately prosperous society' with no Chinese individual left behind - that's the vision for China set out by Chinese President Xi Jinping in a number of important speeches in 2017. 'Moderate' prosperity may seem like a modest goal for a country with more billionaires (609 at last count) than the US. But the 'China Story' is a complex one. The China Story Yearbook 2017: Prosperity surveys the important events, pronouncements, and personalitites that defined 2017. It also presents a range of perspectives, from the global to the individual, the official to the unofficial, from mainland China to Hong Kong and Taiwan. Together, the stories present a richly textured portrait of a nation that in just forty years has lifted itself from universal poverty to (unequally distributed) wealth, changing itself and the world in the process.
Keywords: 330; economic growth; china; government policies; Beijing; Hong Kong